A modest proposal for resolving the eurozone crisis - Yanis Varoufakis; Stuart Holland (Intereconomics, 2012)
This paper presents three simple policies for overcoming the crisis that can be implemented immediately and require none of the moves such as national guarantees or fiscal transfers to which many Europeans are opposed, nor moves towards federation that entail Treaty changes, which electorates are most likely to reject. The logic behind these policy proposals is juxtaposed with the false dilemmas that currently impede clear thinking and immobilise Europe's policymakers.
Keywords: 330; Haushaltsdefizit; Öffentliche Schulden; Bankenkrise; Zahlungsbilanzungleichgewicht; Eurozone; Wirtschaftliche Anpassung; EU-Staaten